Prosodic phrasing and intonation in neutral and subject-narrow-focus sentences of Brazilian Portuguese - Tenani, Luciani Ester [UNESP]; Fernandes-Svartman, Flaviane Romani (My University, 2008)
This work aims at discussing the relationship between prosodic phrasing and intonation structure associated with neutral and subject-narrow-focus sentences in Brazilian Portuguese (BP). The sentences were analyzed in terms of phonological phrases (φ{symbol}s) and tonal events. It is found when subject-narrow-focus occurs, the tonal events of neutral sentences can be affected. We argue that evidences of the syntactic structure can be determined by the relationship between the prosodic phrasing and intonation. Finally, we point out that ours results provide for a better understanding of the syntax-phonology interface in BP.